Study on Human Rights Principles in The Medina Charter and its Implementation In Indonesia - Ridwan, Muannif; Umar, Hasbi; Harun, Hermanto (Future Science, 2021)
The principles of Human Rights are the goals of Islamic shari'a or maqashid al-shari'ah (the philosophy of Islamic law) which has been formulated by al-Ghazali and perfected by as-Syatibi. These principles are summarized in al-dlaruriyah al-khamsah or also called al-huquq al-insaniyah fi al-Islam (human rights in Islam). This concept consists of five basic principles that must be maintained and respected by every individual; Hifzhu al-Din (respect for religious freedom), Hifzhu al-Mal (respect for property), Hifzhu al-Nafs wa al-'Irdl (respect for life, right to life and individual honor), Hifzhu al-'Aql (respect for freedom of thought), and Hifzhu al-Nasl (respect for keeping offspring).This research is examined using a juridical-normative and socio-legal and historical approach. The principles of human rights in the Medina Charter consist of: the principles of justice, equality, freedom of religion, piety, and commanding good and evil. Iimplementation of human rights values ​​in The Medina Charter in Indonesia, the author summarizes it into three areas of life; religion, nation and state consisting of:the field of religious harmony, the field of law and constitution enforcement and the field of socio-political life and the development of the political system. Among the authors' findings, the Medina Charter contains ideas that have strong relevance to the developments and desires of today's world community, especially for Indonesia. The ideas in the Medina Constitution were also absorbed by the founding figures of the Indonesian nation, which can be seen in the Jakarta Charter which later gave birth to Pancasila. The contents of the Medina Charter and Pancasila have in common as a sentence of sawa' (meeting point) diversity or a noble agreement that is constructive, loves, and defends Indonesia, as well as the Medina Charter.